The sense of social influence: pluralistic ignorance in climate change: Social factors play key roles in human behavior. Individuals tend to underestimate how much others worry about climate change. This may inhibit them from taking collective climate action. (22nd October 2018) - Kjeldahl, Esther Michelsen; Hendricks, Vincent F
Abstract : How pluralistic ignorance can inhibit us from taking collective climate action and may affect similar problems such as public resistance to vaccination programs.